2009
DOI: 10.1590/s1516-89132009000700001
|View full text |Cite
|
Sign up to set email alerts
|

An overview on molecular markers for detection of ochratoxigenic fungi in coffee neans

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Our results are partly agreed with that of Sartori et al (2006) found ochratoxin gene amplicon band at 372 bp. While, Fungaro and sartori (2009) and Schmidt et al (2004) found that A. ochraceous gene was expression OCR-A gene at 260 bp. The obvious variance in the above result may be due to technical aspects.…”
Section: Expression Of the Structure Genesmentioning
confidence: 95%
“…Our results are partly agreed with that of Sartori et al (2006) found ochratoxin gene amplicon band at 372 bp. While, Fungaro and sartori (2009) and Schmidt et al (2004) found that A. ochraceous gene was expression OCR-A gene at 260 bp. The obvious variance in the above result may be due to technical aspects.…”
Section: Expression Of the Structure Genesmentioning
confidence: 95%
“…For plant phytopathogens, morphological characterization is still the most used method of fungal identification to this day (Carnielli-Queiroz et al, 2019). However, PCR is already being used to identify the species of fungi in food samples, causing a difference in the final quantity of the product (Fungaro & Sartori, 2009). Another example is the detection of the fungus that causes the disease in the pine.…”
Section: F Verticillioides Detection On Maize Seeds With Different In...mentioning
confidence: 99%
“…Aspergillus and Penicillium species are the major producers of ochratoxins. Ochratoxin A (OTA) is a mycotoxin that is receiving increasing attention worldwide because of its severe nephrotoxicity [8].…”
Section: Introductionmentioning
confidence: 99%